HUBUNGAN ANTARA ADVERSITY QOUTIENT DENGAN CAREER ADAPTABILITY PADA MAHASISWA TINGKAT AKHIR REGULER 1 DI UNIVERSITAS MERCU BUANA KAMPUS MERUYA - Popi Avati; Putri Rahmah Salim (Biopsikososial: Jurnal Ilmiah Psikologi Fakultas Psikologi Universitas Mercubuana Jakarta, 2019)
The purpose of this study is to see the correlation between adversity quotient to career adaptability on regular 1 final student at Mercu Buana University, Meruya Campus. Subjects on this study on regular 1 final student student at meruya campus. The sampling method used is Propotionate Stratifed Random Sampling with amount 208 subjects. The scale career adaptability measure consists of 29 items with reliability of 0.882 and the scale Adversity quotient consists of 31 with reliability of 0.876. Data was taken using a Likert scale technique. Data analysis using Spearman Rho Correlation technique because data distribution is not normal. The results of this study have a value and correlation coefficient r = 0.599 with a significance of p <0.000, which indicates a relationship between adversity qoutient and Career Adaptability to Regular 1 Final Students at Mercu Buana University, Meruya Campus.